In situ grown magnetic COF@MOF with a phosphoserine anchor for in-depth N -glycopeptide analysis in serum - Guo, Yimin; Hua, Shuwen; Wang, Baichun; Wang, Bing; Ding, Chuan-Fan; Yan, Yinghua (Analyst (London), 2023)
A hydrophilic phosphoserine-functionalized magnetic organic framework composite (termed Fe 3 O 4 @COF@MOF-PS) was synthesized by an in situ growth strategy for effective capture of N -glycopeptides. Fe 3 O 4 @COF@MOF-PS exhibited high sensitivity (0.2 fmol μL −1 ), outstanding exclusion of size capability (1 : 10 000), good selectivity (1 : 2000), and reusability (at least 10 times). It also exhibited remarkable performance in the N -glycopeptide analysis in complex biological samples. Via nano-LC-MS/MS analysis, a total of 223 N -glycopeptides with 161 glycosylation sites assigned to 91 glycoproteins and 331 N -glycopeptides with 243 glycosylation sites assigned to 134 glycoproteins were identified in sera from cervical cancer patients and normal controls, respectively. Biological processes and molecular functional analyses indicate that the captured glycoproteins are of significant relevance to cervical cancer, for example, gene coverage or expression of cell adhesion and extracellular matrix structural constituents. Thus, Fe 3 O 4 @COF@MOF-PS not only efficiently captures N -glycopeptides, but also has the possibility of screening potential disease markers and elucidating the process of cervical cancer development.